Credit default swaps and the market for sovereign debt - Ismailescu, Iuliana; Phillips, Blake (Journal of Banking & Finance, 2015)
In this paper, we analyze the determinants and effects of credit default swap (CDS) trading initiation in the sovereign bond market. CDS trading initiation is associated with a 30–150 basis point reduction in sovereign bond yields, with greater yield reductions accruing to higher default risk economies. For countries with high default risk, rated B or lower by Standard and Poor’s, CDS initiation is also associated with significant price efficiency benefits in the underlying market. CDS trading initiation is more likely following increases in local equity index volatility, index spreads for regional and global CDS markets, or depreciation of the local currency relative to the US dollar, and decreases in a country’s ability to service foreign debt. Our results are robust to selection bias controls based on these factors.